(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
This article, based on the example of two countries - Greece and Germany, shows a different approach to their higher education systems for the preparation of qualified specialists in science and culture. Greece, as a country with an ancient and rich historical heritage, attracts many applicants for higher education with high academic records. External governing bodies of higher education in Greece include: central government - the Ministry of Education and Religious Affairs of Greece, district government - regional education authorities, local government - higher education institution. Internal governing bodies include: the University’s Senate, the Rector’s Council, the Rector, the General Assembly, the Student’s Union, Deans of faculties, Heads of departments In Germany, the external governing bodies of higher education are: the central government - the Ministry of Education and Culture, the Permanent Conference of the Ministers of Education and Culture of the Lands, regional. bodies - the Regional Special Ministries, the local government - the university, the Conference or the Council of Rectors of German universities. Internal governing bodies are: the rector or president of the university, the Academic Council, the Student Council, deans of faculties, heads of departments. In Greece, higher education is financed by the state budget, non-state funds, as well as through private payments. In Germany, funding for higher education is provided by the state budget, the states, the Germany Union of Research Assistance and private individuals. For admission to Greek universities, an applicant must provide a certificate of completion of secondary education, and for German universities - ABITUR diploma or competitive selection based on the results of entry exams. For admission to universities in Greece, knowledge of the Greek language is mandatory both for Greeks and for foreigners. The Germany language is mandatory for Germany universities also both for Germans and foreigners. Greek universities have a 10-point grading system, and German universities have a 6-point grading system. In Greek universities, training takes place in three stages: bachelor’s degree - 4-5 years, master’s - 1-3 years, doctoral studies - 3 years. In German universities - basic - 3-4 semesters, main - 4-6 semesters, doctoral studies - 3-4 years. Thus, European higher education is one of the most highly rated forms of education, the rating of which is increasing every year.